Potential of frangipani flower (Plumeria sp.) as a source of antibacterial and antioxidants and its application in the pharmacological activities - CANDRA, KRISHNA PURNAWAN; LESTARI, GISTI MALINDA; PRABOWO, SULISTYO; YULIANI, YULIANI; MARWATI, MARWATI; RACHMAWATI, MAULIDA (Universitas Syiah Kuala, 2024)
Frangipani (Plumeria spp.) was a flowering ornamental plant with several metabolites that can be used as traditional medicine for various diseases such as laxative, anti-itch, anti-inflammatory, diabetic, and malaria. The Frangipani flower showed antibacterial activity against E.coli, P.aeruginosa, S.aureus, C.albicans, S.pyogenes, S.typhi, B.pumilus, B.subtilis, S.dysenteriae, P.mirabilis, P.fluorescens, B.cereus, S.flexneri, and M.furfur. Frangipani flowers also have high antioxidant activity due to their significant phenol and flavonoid content. This study provided an overview of the application of Frangipani flowers for pharmaceutical purposes.